2011
DOI: 10.3390/md9112188
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated-Polysaccharide Fraction from Red Algae Gracilaria caudata Protects Mice Gut Against Ethanol-Induced Damage

Abstract: The aim of the present study was to investigate the gastroprotective activity of a sulfated-polysaccharide (PLS) fraction extracted from the marine red algae Gracilaria caudata and the mechanism underlying the gastroprotective activity. Male Swiss mice were treated with PLS (3, 10, 30 and 90 mg·kg−1, p.o.), and after 30 min, they were administered 50% ethanol (0.5 mL/25 g−1, p.o.). One hour later, gastric damage was measured using a planimeter. Samples of the stomach tissue were also obtained for histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 44 publications
5
18
0
2
Order By: Relevance
“…These data are consistent with those reported in other studies demonstrating that PLSs from algae inhibited ethanol-induced gastric damage by increasing tissue GSH levels through the inactivation of ROS and products of lipid peroxidation [12]. Previous research suggested that ROS-induced damage can be prevented in two ways: by suppressing free-radical generation or by scavenging the free radicals generated [41].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These data are consistent with those reported in other studies demonstrating that PLSs from algae inhibited ethanol-induced gastric damage by increasing tissue GSH levels through the inactivation of ROS and products of lipid peroxidation [12]. Previous research suggested that ROS-induced damage can be prevented in two ways: by suppressing free-radical generation or by scavenging the free radicals generated [41].…”
Section: Resultssupporting
confidence: 92%
“…The PLSs in seaweeds contain substances with great pharmaceutical and biomedical potential [10,11,12]. Recent studies have shown that PLSs extracted from Gracilaria birdiae demonstrated marked antioxidant and anti-inflammatory activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…has been used in the treatment of stomach disorders (Trono, 1999) and the usefulness of carrageenan in ulcer therapy (De Almeida et al, 2011), substantiated the antiulcer activity of G. crassa in the present study. Also, the sulfated algal polysaccharides (Silva et al, 2011) in the seaweeds may provide an effective protection against gastric damage. The fats play a buffering role in reducing and neutralizing the gastric juice and the reported presence of fatty acids in antiulcer compounds isolated from G. verrucosa (Sakagami et al, 1992) substantiated the anti-ulcer activity in G. crassa.…”
Section: Discussionmentioning
confidence: 99%
“…Algae is a rich source of plenty of different varieties of sulphated polysaccharides, which have antioxidant, anti-allergic, anti-inflammatory and anti-coagulant properties ideal for tissue engineering applications [60]. Sulphated polysaccharides like Ulvan extracted from green algae Ulva, Carrageenans from red algae Rhodophyceae and Fucoidan from brown algae Phaeophycophyta [61] have been extensively utilized for synthesis of composite bone scaffolds.…”
Section: Other Algae Based Polysaccharidementioning
confidence: 99%